Avatars and arrows in the brain - Catmur, C; Santiesteban, I; Conway, J; Heyes, C; Bird, G (Elsevier, 2016)
In this Commentary article we critically assess the claims made by Schurz, Kronbichler, Weissengrubler, Surtees, Samson and Perner (2015) relating to the neural processes underlying theory of mind and visual perspective taking. They attempt to integrate research findings in these two areas of social neuroscience using a perspective taking task contrasting mentalistic agents (‘avatars’), with non-mentalistic control stimuli (‘arrows’), during functional Magnetic Resonance Imaging. We support this endeavour whole-heartedly, agreeing that the integration of findings in these areas has been neglected in research on the social brain. However, we cannot find among the behavioural or neuroimaging data presented by Schurz et al. evidence supporting their claim of ‘implicit mentalizing’—the automatic ascription of mental states to another representing what they can see. Indeed, we suggest that neuroimaging methods may be ill-suited to address the existence of implicit mentalizing, and suggest that approaches utilizing neurostimulation methods are likely to be more successful.